Dithiopheneindenofluorene (TIF) Semiconducting Polymers with Very High Mobility in Field-Effect Transistors - Sirringhaus, Henning; Zhang, Weimin; Nikolka, Mark; Hurhangee, Michael; Abdi-Jalebi, Mojtaba; McCulloch, Iain; Chen, Hu; Hayoz, Pascal; Harkin, David; McNeill, Christopher R.; Kirkus, Mindaugas; Neophytou, Marios; et al. (My University, 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim The charge-carrier mobility of organic semiconducting polymers is known to be enhanced when the energetic disorder of the polymer is minimized. Fused, planar aromatic ring structures contribute to reducing the polymer conformational disorder, as demonstrated by polymers containing the indacenodithiophene (IDT) repeat unit, which have both a low Urbach energy and a high mobility in thin-film-transistor (TFT) devices. Expanding on this design motif, copolymers containing the dithiopheneindenofluorene repeat unit are synthesized, which extends the fused aromatic structure with two additional phenyl rings, further rigidifying the polymer backbone. A range of copolymers are prepared and their electrical properties and thin-film morphology evaluated, with the co-benzothiadiazole polymer having a twofold increase in hole mobility when compared to the IDT analog, reaching values of almost 3 cm2 V−1 s−1 in bottom-gate top-contact organic field-effect transistors.
Keywords: CH cyclization; high-mobility; IDT; IDTT; organic field-effect transistors (OFETs); TIF